Preparation method of tin oxide electron transport layer and application thereof in perovskite solar module

By introducing specific additives into the chemical bath deposition method to regulate the electrostatic repulsion and interfacial adsorption of nanoparticles, the problem of non-uniformity in the large-area preparation of tin oxide electron transport layers was solved, achieving efficient tin oxide thin film preparation and improving the performance and scalability of perovskite solar modules.

CN122629454APending Publication Date: 2026-08-25HUAZHONG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610649132.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-12
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

In the process of fabricating tin oxide electron transport layers over large areas, there are problems such as nanoparticle agglomeration leading to uneven film and incomplete coverage, and non-uniformity of the electron transport layer leading to device performance degradation.

Method used

Tin oxide electron transport layers were prepared by chemical bath deposition. By adding a first additive with a zwitterionic structure and a second additive with high electronegativity to the tin precursor solution, the electrostatic repulsion and interfacial adsorption between nanoparticles were controlled, thereby achieving uniform nucleation and continuous growth of nanoparticles.

Benefits of technology

Large-area, dense, and uniform tin oxide thin films were obtained, which improved optical transmittance and electrical uniformity, significantly reduced optical and non-radiative recombination losses during the large-area fabrication process, and improved photoelectric conversion efficiency and fill factor, making them suitable for industrial applications of perovskite solar modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a preparation method of a tin oxide electron transport layer and application of the tin oxide electron transport layer in a perovskite solar module, and belongs to the technical field of new energy photovoltaic materials. The steps are as follows: 1) providing a tin precursor solution for preparing tin dioxide by a bivalent tin chemical bath deposition, and adding a first additive and a second additive to obtain a chemical bath deposition solution; wherein the first additive is a molecule with a phosphoric acid group and a choline group; and the second additive is a polyanion molecule with high electronegativity; 2) immersing a conductive substrate into the chemical bath deposition solution to perform chemical bath deposition; and 3) finally performing cleaning and heat treatment to obtain the tin oxide electron transport layer. The application can obtain a large-area, dense and uniform tin oxide film, and the tin oxide film has excellent optical transmittance, electrical uniformity and interface charge transport capacity, is used in the perovskite solar module, and significantly improves photoelectric conversion efficiency and a fill factor, reduces performance attenuation in an area amplification process, and has excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy photovoltaic materials technology, specifically relating to a method for preparing a tin oxide electron transport layer and its application in perovskite solar modules. Background Technology

[0002] Chemical bath deposition (CBD) is a technique that involves immersing a substrate in a container containing a precursor solution and depositing a thin film on the substrate surface through a chemical reaction. This method has attracted considerable attention due to its simple equipment, low cost, scalability, and ability to prepare large-area uniform films at low temperatures. In the field of perovskite solar cells (PSCs), it has become one of the mainstream processes for preparing electron transport layers (ETLs) such as tin dioxide (SnO2). In perovskite solar cells, the electron transport layer (ETL) is located between the perovskite light-absorbing layer and the electrode. Its core function is to selectively extract and efficiently transport photogenerated electrons while blocking holes, thereby reducing carrier recombination and improving the open-circuit voltage and overall photoelectric conversion efficiency of the device. Furthermore, ETL can also regulate interface energy level matching, improve the crystallinity of the thin film, and play a role in interface passivation and device stability enhancement. For large-area fabrication, a high-quality and uniform electron transport layer has significant practical value: on the one hand, it can maintain good charge transport and low defect density when amplifying device size, avoiding efficiency degradation and leakage problems caused by uneven thickness or pinholes; on the other hand, large-area processable ETL (such as materials prepared by low-temperature solution methods or printing processes) facilitates roll-to-roll production and flexible device manufacturing, significantly reducing manufacturing costs and improving industrialization feasibility, while also improving component consistency, long-term stability, and environmental adaptability, making it one of the key links in promoting perovskite solar cells from the laboratory to commercial applications. However, the following problems still exist in the large-area fabrication process: 1) Nanoparticles are prone to agglomeration, leading to film inhomogeneity; 2) Incomplete coverage on rough conductive substrates; 3) The inhomogeneity of the electron transport layer leads to significant performance degradation during device size scaling.

[0003] Therefore, there is an urgent need to find a method suitable for large-area preparation of tin oxide electron transport layers to solve the problems of unevenness and numerous defects in large-area tin oxide electron transport layer films in the traditional CBD method. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing a tin oxide electron transport layer and its application in perovskite solar modules. This method is suitable for preparing large-area tin oxide electron transport layers, and the prepared tin oxide electron transport layer film has continuous and uniform coverage; a dense surface without obvious pinholes or particle agglomeration; and high optical transmittance.

[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A method for preparing a tin oxide electron transport layer is provided, comprising the following steps: 1) Provide a tin precursor solution for preparing tin dioxide by chemical bath deposition of divalent tin. Add a first additive and a second additive to the tin precursor solution to obtain a chemical bath deposition solution. The first additive is a molecule with a zwitterionic structure and has phosphate and choline groups. The second additive is a polyanionic molecule with high electronegativity. 2) Immerse the conductive substrate in the chemical bath deposition solution obtained in step 1) and perform chemical bath deposition under heating conditions; 3) The sample deposited in step 2) is cleaned and heat-treated to obtain the tin oxide electron transport layer.

[0006] According to the above scheme, in step 1), the tin precursor solution for preparing tin dioxide by chemical bath deposition of divalent tin includes a divalent tin source and a slowly releasing OH group. - The ion-releasing agent and acid regulator are prepared by dissolving a divalent tin source, a slow-release agent, and an acid regulator in water. Divalent tin undergoes hydrolysis, oxidation, and dehydration reactions to generate SnO2 nanoparticles. Specifically, the divalent tin source provides Sn... 2+ Ions, acid regulators provide a strongly acidic initial environment, effectively inhibiting premature and uncontrolled hydrolysis of divalent tin source tin and precursors, while maintaining the colloidal stability of CBD solutions. Sn 2+ After hydrolysis and oxidation in an acidic environment, ions are converted into Sn. 4+ The ion-release agent gradually hydrolyzes and slowly decomposes under the thermal activation conditions of deposition, continuously and uniformly releasing OH-. - The ions, thus slowly increasing the pH of the reaction system, Sn 2+ Ions are converted into SnO2 nanoparticles through hydrolysis, oxidation and dehydration reactions.

[0007] Preferably, in the tin precursor solution for preparing tin dioxide by chemical bath deposition of divalent tin: the tin source contains Sn 2+ The concentration is 1~20 mM, the sustained-release agent concentration is 1~500 mM, and the acid regulator volume fraction is 0.1~2%.

[0008] Preferably, the tin source is stannous chloride (SnCl2) or its hydrate; the slow-release agent is urea; and the acid regulator is hydrochloric acid.

[0009] According to the above scheme, the tin precursor solution for preparing tin dioxide by chemical bath deposition of divalent tin also includes a complexing agent with a concentration of 0.01~0.1 mM. Preferably, the complexing agent is mercaptoacetic acid.

[0010] According to the above scheme, in step 1), the first additive is at least one of phosphoric acid choline, glycerophosphocholine or lysophosphatidylcholine; the second additive is at least one of hexametaphosphate, tetrapolyphosphate, tripolyphosphate, pyrophosphate, phytic acid, terephthalic acid or sodium tripolyphosphate.

[0011] According to the above scheme, in step 1), the first additive and the second additive are dissolved in a small amount of water before being added to the tin precursor solution. Preferably, the mass-to-volume ratio of the first additive and the second additive to water is 1 mg / 20~30 μL.

[0012] According to the above scheme, in step 1), the concentration of the first additive in the chemical bath deposition solution is 0.001~0.5mM; preferably 0.1~0.3mM; the molar ratio of the first additive to the second additive is 1:1~15:1, preferably 5:1~10:1.

[0013] According to the above scheme, in step 2), the chemical bath deposition temperature is 50~90℃, preferably 55~75℃; the reaction time is 8~24h, preferably 12~18h.

[0014] According to the above scheme, in step 2), the size of the conductive substrate is 0.5 × 0.5 cm. 2 ~100×100cm 2 Preferably 1×1 cm 2 ~15×15 cm 2 .

[0015] According to the above scheme, in step 2), the conductive substrate is fluorine-doped tin oxide glass, FTO.

[0016] According to the above scheme, in step 2), the pretreatment process of the conductive substrate is as follows: ultrasonic cleaning in detergent solution for 15-30 min, ultrasonic cleaning in deionized water for 15-30 min, ultrasonic cleaning in acetone for 15-20 min, ultrasonic cleaning in anhydrous ethanol for 15-20 min, followed by ultraviolet ozone or plasma treatment for 10-20 min to remove surface organic contaminants and improve hydrophilicity.

[0017] According to the above scheme, in step 3), after the deposition is completed, the substrate is removed and rinsed with deionized water (to remove residual precursors), and then dried with nitrogen.

[0018] According to the above scheme, in step 3), heat treatment is performed to improve the crystallinity and adhesion of the film. The heat treatment temperature is 120~180 ℃ and the time is 30~90 min.

[0019] According to the above scheme, in step 3), the prepared tin oxide electron transport layer is at least 10 × 10 cm⁻¹. 2 The standard deviation of transmittance over the area is less than 0.6%.

[0020] This invention provides an application of the tin oxide electron transport layer prepared by the above method in a perovskite solar module.

[0021] This invention provides a method for preparing a tin oxide electron transport layer. This method is based on a chemical bath deposition process and simultaneously introduces two types of functional additives into the reaction system to obtain a large-area, uniform, and dense tin oxide electron transport layer; wherein: In the preparation of the SnO2 electron transport layer (ETL) via chemical bath deposition (CBD), divalent tin is chemically deposited to generate SnO2 nanoparticles. During nanoparticle formation, a complexing agent coordinates with the newly formed nanoparticles, partially neutralizing their surface positive charge, reducing electrostatic repulsion between the nanoparticles and the substrate, and promoting nanoparticle assembly. Simultaneously, the phosphate groups of the first additive bind to the surface of the SnO2 nanoparticles, while the choline groups are exposed outwards, enhancing the electrostatic repulsion between SnO2 nanoparticles, thereby improving colloidal stability and preventing aggregation, while also imparting positive charge to the SnO2 nanoparticles. Furthermore, highly electronegative second additive molecules preferentially adsorb onto the conductive substrate, forming a negatively charged interfacial layer that attracts positively charged SnO2 nanoparticles, promoting deposition. After the initial adsorption step, the deposited nanoparticles gradually rearrange laterally and stack vertically through interparticle aggregation, ultimately forming a dense and continuous SnO2 electron transport layer.

[0022] The beneficial effects of this invention are as follows: 1. This invention provides a method for preparing a tin oxide electron transport layer. During chemical bath deposition, two functional additives are introduced: a first additive regulates the electrostatic repulsion between tin oxide nanoparticles, and a second additive enhances the interfacial adsorption between the nanoparticles and the conductive substrate. This achieves synergistic regulation of nanoparticle-nanoparticle and nanoparticle-substrate interactions, guiding uniform nucleation and continuous growth of nanoparticles during deposition to obtain a large-area, dense, and uniform tin oxide film. This method achieves a balance between particle dispersion and interfacial deposition behavior, which is difficult to achieve with traditional techniques, and is suitable for preparing large-area tin oxide electron transport layers. The electron transport layer obtained by this invention exhibits excellent optical transmittance, electrical uniformity, and interfacial charge transport capabilities, significantly reducing optical and non-radiative recombination losses during large-area fabrication. When used in perovskite solar modules, it achieves a photoelectric conversion efficiency (PCE) of over 20% and a fill factor (FF) of over 75%, and is suitable for small-area (1 cm²) applications. 2 The device was expanded to a large area (65.24 cm²).2 When used in the assembly, its PCE decreased by only 3.66%, significantly reducing the performance degradation of the device during the area scaling process. It has excellent overall performance and broad application prospects.

[0023] 2. The method of the present invention is mild and highly scalable, which is conducive to industrial application. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the mechanism by which phosphocholine (PC) and hexametaphosphate (HMP) synergistically electrostatically regulate the generation of tin oxide in Example 1 of the present invention.

[0025] Figure 2 The images show a comparison of the morphology of tin oxide films under different conditions and deposition times in Example 1 and Comparative Examples 1-2 of this invention, as well as simplified diagrams of the deposition process. The scales of the smaller images are the same.

[0026] Figure 3 The optical performance test results of the tin oxide thin films in Example 1 and Comparative Example 1 of the present invention are shown below; wherein: (a) transmittance spectrum of SnO2 thin film; (b) transmittance spectrum of SnO2-PCHMP thin film; (c) transmittance spectrum of SnO2 thin film and SnO2-PCHMP thin film at a wavelength of 400 nm; (d) angle-resolved transmittance (ART) spectrum of SnO2 thin film and SnO2-PCHMP thin film.

[0027] Figure 4 The following are the electrical and interface performance test results of the tin oxide films in Example 1 and Comparative Example 1 of the present invention; wherein: (a) O 1s XPS spectra of SnO2 film and SnO2-PCHMP film; (b) electron mobility of SnO2 film and SnO2-PCHMP film; (c) KPFM images of SnO2 film and SnO2-PCHMP film; (d) linear surface potential line distribution of SnO2 film and SnO2-PCHMP film.

[0028] Figure 5 The graph shows a performance comparison of perovskite solar cell devices and modules prepared using the tin oxide electron transport layers obtained in Examples 1-3. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be modified or substituted in various ways as long as they do not conflict with each other.

[0030] Example 1 A method for preparing a tin oxide electron transport layer based on the synergistic regulation of phosphocholine / hexametaphosphate is provided, comprising the following steps: 1) Substrate treatment Select an FTO conductive glass with dimensions of 10 cm × 10 cm, and ultrasonically clean it in detergent, deionized water, acetone and ethanol for 20 min each, and then treat it with ultraviolet ozone for 15 min.

[0031] 2) Preparation of precursor solution Add 500 mg of urea, 500 μL of hydrochloric acid, 1 μL of mercaptoacetic acid, and 109.6 mg of stannous chloride to 40 mL of deionized water and stir until completely dissolved. Then, take 20 mL of the solution and dilute it in 100 mL of deionized water.

[0032] 3) Preparation of additive solution Dissolve 1 mg sodium hexametaphosphate (HMP) and 3 mg phosphocholine (PC) in 100 μL of deionized water, then add them to the precursor solution and stir thoroughly to form a homogeneous system.

[0033] 4) Deposition process The treated FTO substrate was placed in the above solution and reacted in a water bath at 60 °C for 16 hours.

[0034] 5) Post-processing After deposition, the sample was removed, rinsed with deionized water and dried with nitrogen, and then annealed at 150°C for 60 min to obtain a tin oxide film containing two additives, denoted as SnO2-PCHMP.

[0035] 6) Results and Effects The resulting tin oxide film has the following properties: at a depth of 10 × 10 cm... 2 It achieves continuous and uniform coverage within the range; the surface is dense with no obvious pinholes or particle agglomeration; it has high optical transmittance and spatial fluctuation of less than 1%; and it significantly improves the short-circuit current density and fill factor of perovskite devices.

[0036] Example 2 The specific operation is the same as in Example 1, except that the area of ​​the FTO conductive glass substrate is changed to 1.8 cm × 2.2 cm.

[0037] Example 3 The specific operation is the same as in Example 1, except that the area of ​​the FTO conductive glass substrate is changed to 5 cm × 5 cm.

[0038] Perovskite solar cells and modules were fabricated using the tin oxide electron transport layers obtained in Examples 1-3, respectively. The specific structure of the perovskite solar cell was: FTO / SnO2-PCHMP (ETL) / perovskite / spiro-OMeTAD (spirodifluorene-based hole transport material) / Au. The electron transport layer obtained in Example 2 was used for a single perovskite solar cell; the electron transport layers obtained in Examples 3 and 1 were used to fabricate perovskite solar modules, respectively, by connecting 6 sub-cells (for a 5×5 cm² module) and 10 sub-cells (for a 10×10 cm² module) on an FTO / glass substrate, connected in series using laser scribing technology. Performance tests were conducted on the perovskite solar cell devices and modules; the performance comparison chart is shown below. Figure 5 .

[0039] Comparative Example 1 The specific operation is the same as in Example 1, except that the additive solution preparation process in step (3) is omitted, and an additive-free tin oxide film is obtained, which is denoted as SnO2.

[0040] Comparative Example 2 The specific operation is the same as in Example 1, except that sodium hexametaphosphate is not added in step (3), only phosphocholine is added to obtain a tin oxide film containing the additive phosphocholine, which is denoted as SnO2-PC.

[0041] Figure 1 This is a schematic diagram illustrating the mechanism of synergistic electrostatic regulation of tin oxide formation by phosphoric acid choline (PC) and hexametaphosphate (HMP) in Example 1 of this invention. The diagram shows that during the formation of SnO2 nanoparticles, the phosphate terminus of the phosphoric acid choline (PC) molecule coordinates with the surface of the SnO2 nanoparticles. The outward-aligned choline groups significantly enhance the electrostatic repulsion between nanoparticles, thereby effectively improving the stability of the colloid and inhibiting particle aggregation. Simultaneously, the highly electronegative HMP molecules preferentially adsorb onto the FTO substrate surface, forming a negatively charged interface layer. This layer guides the deposition of positively charged SnO2 nanoparticles through electrostatic attraction. Subsequently, driven by the synergistic interaction between particles and the interface effect, these fixed particles achieve continuous lateral and longitudinal growth through controlled attachment and aggregation, ultimately constructing a dense, uniform, and high-performance SnO2 electron transport layer.

[0042] Figure 2The figures show a comparison of the morphology of tin oxide films deposited at different times in Example 1 and Comparative Examples 1-2 of this invention. The figures show that comprehensive morphological analysis was performed on the SnO2 samples in Comparative Example 1, SnO2-PC samples in Comparative Example 2, and SnO2-PCHMP samples in Example 1 at different reaction stages. Scanning electron microscopy (SEM) revealed that the growth of nanoparticles and film coverage exhibited a clear evolutionary pattern over time during the co-precipitation deposition process. After 4 hours of deposition, the SnO2 sample in Comparative Example 1 showed large, irregular aggregates, consistent with its rapid and uncontrolled nucleation-growth process. In contrast, the SnO2-PC sample in Comparative Example 2 and the SnO2-PCHMP sample in Example 1 showed smaller and more uniform nanoparticles, indicating that PC imparted better colloidal stability. By 8 hours, the SnO2-PCHMP sample in Example 1 began to form a continuous thin layer with uniform nanoparticle distribution and early lateral aggregation, while the SnO2 in Comparative Example 1 showed uneven accumulation on the pre-deposited SnO2. After 16 hours, the PCHMP-controlled film completely covered the substrate and exhibited a compact morphology, while the SnO2 in Comparative Example 1 showed over-accumulation and poor uniformity in the recessed areas. These morphological differences became more pronounced after annealing. The SnO2 in Comparative Example 1 showed extensive nanoparticle aggregation (highlighted with blue circles) and excessive particle accumulation in the FTO recessed areas (highlighted with red circles), indicating poor film compactness and high roughness. Meanwhile, the SnO2-PCHMP of Example 1 was more compact than the SnO2-PC of Comparative Example 2. This improvement in film quality can be attributed to the synergistic regulation of nanoparticle-nanoparticle and nanoparticle-substrate interactions in the PCHMP strategy, which promotes complete and uniform coverage of SnO2 nanoparticles on the FTO surface. This results in higher density, smoothness, and structural integrity, and significantly enhanced adhesion to the substrate.

[0043] Figure 3 The figures show the optical performance test results of the tin oxide thin films obtained in Example 1 and Comparative Example 1 of this invention; wherein: Figure 3 a and Figure 3 b shows the UV-Vis transmission spectra of SnO2 and SnO2-PCHMP films, displaying a 10 × 10 cm⁻¹ spectrum. 2 The uniformity of SnO2-PCHMP thin films over a large area; Figure 3 c shows the transmittance (T400) of 10 representative samples at a wavelength of 400 nm. (10 × 10⁻⁶ cm⁻¹) 2The standard deviation of transmittance in different regions of the SnO2-PCHMP film was only 0.44%, demonstrating its excellent uniformity over a large scale, while the SnO2 film of Comparative Example 1 showed a higher standard deviation of 0.80%. Furthermore, Figure 3 Angle-resolved transmission (ART) measurements showed that, in the 300-800 nm wavelength range, regardless of the incident angle, the SnO2-PCHMP film consistently outperformed the control sample, highlighting its ability to mitigate optical losses over a wide angle.

[0044] Figure 4 The figures show the electrical and interface performance test results of the tin oxide films obtained in Example 1 and Comparative Example 1 of this invention; the figures show multi-dimensional characterization by XPS, charge migration test, and KPFM. The introduction of PCHMP significantly optimizes the physicochemical properties of the SnO2 electron transport layer. Regarding the chemical composition, such as... Figure 4 As shown in Figure a, the high-resolution O 1s spectrum exhibits two distinct peaks. The main peak is located at 530.9 eV, corresponding to the O-Sn bond in the metal oxide SnO2, while the secondary peak is located at 532.2 eV, related to oxygen vacancies and chemisorbed hydroxyl groups. The high-resolution O 1s spectrum confirms that due to the electron-donating ability of the phosphate groups in the PC molecule and their coordination with the undercoordinated tin atoms on the surface, the oxygen vacancy content is significantly reduced from 34.35% in the control group to 19.37%, thus neutralizing the oxygen vacancy defects. Regarding electrical properties, such as… Figure 4 As shown in b, the modified SnO2-PCHMP exhibits a higher current density, with electron mobility increasing from 2.77 × 10⁻⁶. -4 cm 2 V -1 s -1 Increased to 4.21×10 -4 cm 2 V -1 s -1 Simultaneously, Kelvin probe force microscopy (KPFM) was used to evaluate the surface potential distribution of the SnO2 electron transport layer regulated by control group SnO2 and PCHMP, such as... Figure 4 As shown in Figure c, the average contact potential of the SnO2-PCHMP sample is 497.2 mV, which is about 50 mV higher than that of Comparative Example 1 (446.5 mV). This indicates that the work function (WF) of SnO2 is reduced due to PCHMP modulation, which is beneficial for optimizing energy level matching and reducing the electron injection barrier, thereby significantly improving the open-circuit voltage (Vc). OC ) and charge extraction efficiency. Figure 4Figure d shows the corresponding linear surface potential curves. The control film exhibits significant potential fluctuations with a potential difference of 34.7 mV, consistent with its non-uniform surface morphology and electrical inhomogeneity. These characteristics may lead to suboptimal interfacial level alignment and nonradiative recombination at the perovskite / ETL interface. In contrast, the PCHMP-regulated SnO2 film shows a more uniform surface potential distribution, with a significantly reduced potential difference to 27.6 mV.

[0045] Figure 5 The figure shows a performance comparison of perovskite solar cell devices and modules fabricated using the tin oxide electron transport layers prepared in Examples 2, 1, and 3. The optimized 1.8 × 2.2 cm⁻¹ solar cell is also shown in the figure. 2 (Example 2, working area is 1 cm) 2 PSC and the prepared 5×5 cm 2 (Example 3, working area is 15.82 cm²) 2 ) and 10×10 cm 2 (Example 1, working area is 65.24 cm²) 2 The JV curve of the perovskite solar module is shown in the figure, with the inset showing a 10×10 cm module. 2 Photo of the module. As shown in the figure, the PSC in Example 2 achieves a photoelectric conversion efficiency of 24.70%, an open-circuit voltage of 1.156 V, and a short-circuit current of 25.93 mA cm⁻¹. -2 With a fill factor of 82.4%, this is the highest reported photoelectric conversion efficiency (PCE) for this size of PSC based on a CBD-treated SnO2 electron transport layer. The module in Example 3 achieved a PCE of 22.45%, with an open-circuit voltage of 6.820 V and a short-circuit current of 4.21 mA cm⁻¹. -2 The fill factor is 78.2%. The module in Example 1 achieved a photoelectric conversion efficiency of 21.04%, an open-circuit voltage of 11.252 V, and a short-circuit current of 2.49 mA cm⁻¹. -2 The fill factor is 75.1%. Perovskite solar modules, benefiting from the synergistic electrostatic interaction modulation of the SnO2 electron transport layer, achieve the highest photoelectric conversion efficiency (PCE) among all reported modules of its class. Furthermore, this is achieved despite the small area (1 cm²). 2 The device was expanded to a large area (65.24 cm²). 2 When the component is used, its PCE decreases by only 3.66%, significantly reducing the performance degradation of the device during the area scaling process.

[0046] The results show that precise control of electrostatic interactions between particles and interfaces is crucial for suppressing inhomogeneities caused by the electron transport layer, thereby minimizing the increase in area-dependent series resistance and enabling large-area solar modules to approach the efficiency of their smaller-area counterparts, effectively promoting the scaling up of perovskite solar modules.

[0047] It should be understood that those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A method for preparing a tin oxide electron transport layer, characterized in that, The steps include the following: 1) Provide a tin precursor solution for preparing tin dioxide by chemical bath deposition of divalent tin. Add a first additive and a second additive to the tin precursor solution to obtain a chemical bath deposition solution; wherein the first additive is a molecule with phosphate and choline groups; and the second additive is a polyanionic molecule with high electronegativity. 2) Immerse the conductive substrate in the chemical bath deposition solution obtained in step 1) and perform chemical bath deposition under heating conditions; 3) The sample deposited in step 2) is cleaned and heat-treated to obtain the tin oxide electron transport layer.

2. The preparation method according to claim 1, characterized in that, In step 1), the tin precursor solution includes a divalent tin source and a slowly releasing OH group. - The ion-releasing agent and acid-regulating agent are prepared by dissolving a divalent tin source, a releasing agent, and an acid-regulating agent in water; wherein: the divalent tin source contains Sn 2+ The concentration is 1~20 mM, the sustained-release agent concentration is 1~500 mM, and the acid regulator volume fraction is 0.1~2%.

3. The preparation method according to claim 2, characterized in that, The divalent tin source is stannous chloride or its hydrate; the slow-release agent is urea; and the acid regulator is hydrochloric acid.

4. The preparation method according to claim 2, characterized in that, The tin precursor solution also includes a complexing agent with a concentration of 0.01~0.1 mM.

5. The preparation method according to claim 4, characterized in that, The complexing agent is mercaptoacetic acid.

6. The preparation method according to claim 1, characterized in that, In step 1), the first additive is at least one of phosphoric acid choline, glycerophosphocholine, or lysophosphatidylcholine; the second additive is at least one of hexametaphosphate, tetrapolyphosphate, tripolyphosphate, pyrophosphate, phytic acid, terephthalic acid, or sodium tripolyphosphate.

7. The preparation method according to claim 1, characterized in that, In step 1), the concentration of the first additive in the chemical bath deposition solution is 0.001~0.5mM; the molar ratio of the first additive to the second additive is 1:1~15:

1.

8. The preparation method according to claim 1, characterized in that, In step 2), the chemical bath deposition temperature is 50~90℃ and the reaction time is 8~24h; in step 3), the heat treatment temperature is 120~180℃ and the time is 30~90min.

9. The preparation method according to claim 1, characterized in that, In step 2), the size of the conductive substrate is 0.5 × 0.5 cm. 2 ~100×100cm 2 .

10. The application of a tin oxide electron transport layer prepared by the preparation method according to any one of claims 1-9 in a perovskite solar module.